Uptake of Cervical Cancer Screening and Its Barriers Using Health Belief Model Among Health Professionals Working in Public Hospitals in South Gondar Zone, Northcentral Ethiopia: Multicenter Cross-Sectional Study - Tigabu Munye Aytenew; Yohannes Tesfahun Kassie; Solomon Demis Kebede (Women's Health Reports)
Background: Cervical cancer is a malignant neoplasm that originates in the cervix, and it is a leading cause of mortality, with 270,000 deaths every year globally. Of these, 85% occur in developing countries, including Ethiopia. Routine cervical cancer screening and early treatment can prevent up to 80% of cervical cancers. Health professionals are expected to screen for and be screened for cervical cancer. However, there is limited information about the uptake of cervical cancer screening among health professionals in the study area. Objective: This study aimed to determine the magnitude of cervical cancer screening uptake and identify its barriers among health professionals. Methods: A multicenter cross-sectional study design was conducted among health professionals from December 01 to 30, 2022. A total of 164 respondents were included in the study, and simple random sampling was used to select the respondents. Variables with a p-value of <0.05 at 95% confidence interval (CI) were considered significantly associated with the outcome variable. Results: Of the total respondents, 112 (68.3%) were younger than the age of 30 years, with a mean age of 29.4 years ranging from 21 to 45 years. Seventy-nine of the respondents (48.2%) have work experience of 6–10 years, and 103 (62.8%) are nurses in profession. In this study, the magnitude of cervical cancer screening uptake was 28.1% (95% CI: 27.7%–35.6%). Moreover, attitude (adjusted odds ratio [AOR] = 3.3, 95% CI: 2.1–5.1), age at first sexual intercourse (AOR = 2.1, 95% CI: 1.3–3.4), having history of sexually transmitted infections (STIs; AOR = 3.6, 95% CI: 1.5–11.6), knowing someone who had been screened (AOR = 2.9, 95% CI: 1.8–4.8), and cervical cancer screening training (AOR = 1.6, 95% CI: 1.1–2.9) were significantly associated with cervical cancer screening. Conclusion: Generally, this study reported that the magnitude of cervical cancer screening uptake was low. The study also indicated that attitude, age at first sexual intercourse, history of STIs, knowing someone who had been screened, and training of cervical cancer screening were independent predictors of uptake of cervical cancer screening.